'An Underworld in Education': The Demise of Missouri's Medical Diploma Mills. (9th October 2018) - Johnson, David Alan
Summary: A 1923 exposé of medical diploma mills by the St. Louis Star highlighted vulnerabilities in American medical education and licensing. Disparities in quality characterised early twentieth-century American medical schools. In some states, poorly drawn educational chartering laws allowed schools to issue diplomas on the basis of minimal or no legitimate educational experience. Meanwhile, licensing laws conferred an economic value to the medical licence as a credential. This environment provided an opportunity for two outlier schools and several eclectic medical boards to operate in unethical and criminal fashion. Reporter Harry Brundidge's articles led to the dismantling of one state medical board (Connecticut), reorganisation in another (Missouri) and a fight for existence in a third (Arkansas). The episode also presented an opportunity for structural and philosophical reform of state medical boards. These boards remained insular, professionally dominated bodies focused predominantly on their licensing function with limited interest in an expanded disciplinary role.